Brexit: the politics of a bad idea (London, 2016)
"The United Kingdom will take the most important decision of this millennium so far on 23rd June 2016 when it decides whether to remain in or to leave the European Union. The huge uncertainty surrounding the outcome of this momentous vote not only in the UK but across the whole of Europe is already taking a heavy toll – economically as well as politically. What’s more, the poor quality of debate on a topic as complex as EU membership carries the risk that this crucial vote is decided not on the basis of the best available information and analysis but on gut feeling and short-term mood swings. This is no way to decide upon fundamental issues of democracy and sovereignty for years to come. We have therefore decided to bring together the key arguments developed by some leading thinkers from within and without the UK to show why Brexit is a bad political idea. New in-depth economic analyses of the most likely effects of Brexit are published virtually every single day but there is a surprising lack of comprehensive political analysis with the same level of intensity and depth. This book seeks to close this gap."